Investigating the relationship between teachers' distributed leadership characteristics and school effectiveness in selected secondary schools in Katsina State Nigeria - Yangaiya, Salisu Abba (Institute of Education, International Islamic University Malaysia, 2013)
The purpose of this study is to investigate the relationship between teachers' distributed leadership characteristics and school effectiveness in selected secondary schools in Katsina state, Nigeria. Teacher commitment and teacher empowerment were used as mediating variables in the study. A total of 550 junior and senior secondary school teachers completed the survey questionnaires, out of which 499 respondents were used in the study. Principal Component Analysis (PCA) and Confirmatory Factor Analysis (CFA) were conducted to extract the underlying dimensions and assess the psychometric properties of the scales. SPSS (version 16.0) and AMOS (version 16.0) were used in the analyses. The findings of the study indicate that there are direct statistically significant relationships between distributed leadership and school effectiveness, teacher empowerment and teacher commitment. Besides, teacher commitment and teacher empowerment mediate the relationship between distributed leadership and school effectiveness. The findings suggest that distributed leadership can be used in Katsina state secondary schools to enhance school effectiveness. The results are beneficial since there have been few published studies on distributed leadership and its influence on secondary school's effectiveness in Katsina state in particular and Nigeria in general. Moreover, the study enriches the existing literature by contributing a model depicting the influence of distributed leadership on school effectiveness. The study also contributes to the existing literature and the body of knowledge by finding that teacher empowerment alone does not mediate the relationship between distributed leadership and school effectiveness.